Reliability and diagnostics of the electrical equipment industrial enterprises and power plants - Shevchenko, V. V. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The electric power industry is undergoing great change driven by rapid technological transformation, concern over climate change, and evolving market structures. As a result, there is a need for new models to help the industry better utilize resources in a time of increasing uncertainty and to help government policy makers better understand the impacts of their decisions. The discipline "Reliability and diagnostics of electrical equipment" introduces students to the main electrical equipment power plants and industrial enterprises, forms knowledge about the organization of installation, maintenance, repair and diagnostics of electrical machines (EM) and transformers. To study the discipline, knowledge of the general EM course and design courses, manufacturing technology and diagnostics of EM and transformers, normative documents on maintenance of electrical equipment (EЕ) are required. In the studying the discipline, the following questions are considered: - determination of the list of main electrical equipment of power plants, substations and industrial enterprises; - studying of design features, diagnostics, maintenance of electrical equipment of power plants, substations and industrial enterprises in accordance with the features of technological production processes; – study of the rules for choosing EM and transformers for a given load and electric drive, means and methods that increase the reliability of their work; – study of means diagnostic the condition of EM and transformers, the mean of repair and adjustment of EM and transformers. In addition, as a result of studying the discipline, the student must know the rules of transportation and installation of EM and transformers; rules for commissioning and commissioning and acceptance tests of EM and transformers; study of methods of monitoring EM and transformers during operation.
Keywords: methodical instructions; control tasks; reliability of electrical equipment; diagnostics of electrical equipment; power plants; electric power engineering